A Comparative Study of Top-Down and Bottom-Up Carbon Nanodots and Their Interaction with Mercury Ions - Federico Bruno; Alice Sciortino; Gianpiero Buscarino; Maria Laura Soriano; Ángel Ríos; Marco Cannas; Franco Gelardi; Fabrizio Messina; Simonpietro Agnello (Nanomaterials, 2021)
We report a study of carbon dots produced via bottom-up and top-down routes, carried out through a multi-technique approach based on steady-state fluorescence and absorption, time-resolved fluorescence spectroscopy, Raman spectroscopy, infrared spectroscopy, and atomic force microscopy. Our study focuses on a side-to-side comparison of the fundamental structural and optical properties of the two families of fluorescent nanoparticles, and on their interaction pathways with mercury ions, which we use as a probe of surface emissive chromophores. Comparison between the two families of carbon dots, and between carbon dots subjected to different functionalization procedures, readily identifies a few key structural and optical properties apparently common to all types of carbon dots, but also highlights some critical differences in the optical response and in the microscopic mechanism responsible of the fluorescence. The results also provide suggestions on the most likely interaction sites of mercury ions at the surface of carbon dots and reveal details on mercury-induced fluorescence quenching that can be practically exploited to optimize sensing applications of carbon dots.